Protective effect of heme oxygenase induction in ethinylestradiol-induced cholestasis - Muchova, Lucie (J Cell Mol Med, 2015)
Estrogen-induced cholestasis is characterized by impaired hepatic uptake and biliary bile acids secretion because of changes in hepatocyte transporter expression. The induction of heme oxygenase-1 (HMOX1), the inducible isozyme in heme catabolism, is mediated via the Bach1/Nrf2 pathway, and protects livers from toxic, oxidative and inflammatory insults. However, its role in cholestasis remains unknown. Here, we investigated the effects of HMOX1 induction by heme on ethinylestradiol-induced cholestasis and possible underlying mechanisms. Wistar rats were given ethinylestradiol (5 mg/kg s.c.) for 5 days. HMOX1 was induced by heme (15 μmol/kg i.p.) 24 hrs prior to ethinylestradiol. Serum cholestatic markers, hepatocyte and renal membrane transporter expression, and biliary and urinary bile acids excretion were quantified. Ethinylestradiol significantly increased cholestatic markers (P ≤ 0.01), decreased biliary bile acid excretion (39%, P = 0.01), down-regulated hepatocyte transporters (Ntcp/Oatp1b2/Oatp1a4/Mrp2, P ≤ 0.05), and up-regulated Mrp3 (348%, P ≤ 0.05). Heme pre-treatment normalized cholestatic markers, increased biliary bile acid excretion (167%, P ≤ 0.05) and up-regulated hepatocyte transporter expression. Moreover, heme induced Mrp3 expression in control (319%, P ≤ 0.05) and ethinylestradiol-treated rats (512%, P ≤ 0.05). In primary rat hepatocytes, Nrf2 silencing completely abolished heme-induced Mrp3 expression. Additionally, heme significantly increased urinary bile acid clearance via up-regulation (Mrp2/Mrp4) or down-regulation (Mrp3) of renal transporters (P ≤ 0.05). We conclude that HMOX1 induction by heme increases hepatocyte transporter expression, subsequently stimulating bile flow in cholestasis. Also, heme stimulates hepatic Mrp3 expression via a Nrf2-dependent mechanism. Bile acids transported by Mrp3 to the plasma are highly cleared into the urine, resulting in normal plasma bile acid levels. Thus, HMOX1 induction may be a potential therapeutic strategy for the treatment of ethinylestradiol-induced cholestasis.